Actualizing Islamic Economic Law in the Digital Era: A Study of the Application of Khiyar al-Majlis in Electronic Contracts - Muhammad, Pauzi; Arianti, Farida; Masum, Ahmad; Rani, Marnia (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research was motivated by the emergence of electronic contracts, while every contract contains provisions and implementation of khiyar al-majlis, namely the right of the parties to the transaction to choose to continue or cancel a business transaction as long as the parties are still present at the transaction location. Due to the unclear existence and mechanism for implementing khiyar al-majlis in electronic contracts, this research was urgent. The aim of this research was to determine the existence and mechanism for implementing khiyar al-majlis in electronic contracts. The research method used was normative legal research with a systematic legal approach. Researchers use secondary data or legal materials obtained and processed using selective categorization. All of this legal material was grouped based on criteria that were appropriate to the problems and themes, then analyzed descriptively and analytically. The law of khiyar al-majlis was described and analyzed with explanation, study, systematization, interpretation, and evaluation. The results of this research showed that the existence of khiyar al-majlis in electronic contracts was only legal because the parties were not in the same transaction location as in conventional contracts. Then, the mechanism for implementing khiyar al-majlis could occur directly or indirectly in electronic contracts. This study contributes to the development and actualization of Islamic economic law in the digital era.